Establishment Of Callus And Cell Suspension Cultures Of Clitoria Ternatea For The Production Of Pentacyclic Triterpenoids - Teoh, Siew Chin (2025)
Clitoria ternatea, or commonly known as butterfly pea, is a perennial herbaceous plant belonging to the fabaceae family. Renowned for its medicinal properties, the flowers, leaves, stems, and roots consist of a rich array of novel phytochemical compounds associated with medicinal and pharmacological properties, including pentacyclic triterpenoids particularly taraxerol and lupeol, known for their memory-enhancing properties. The current study aims to establish callus and cell suspension cultures from cotyledon explants of c. Ternatea for production of novel plant secondary metabolites associated to the mammalian neuroprotective mechanism. The in vitro cotyledon explants were subjected to callus induction and proliferation in treatments of plant growth regulators (2,4-d, naa, bap, kinetin and tdz) and sucrose concentrations (15 g/l and 30 g/l) in half-strength murashige and skoog (1962) media. The optimal proliferation media were then used for the establishment of cell suspension cultures, followed by gc-ms analysis to identify and quantify the pentacyclic triterpenoids.